Ensiklopedia Mukjizat Al-Qur'an Dan Hadis Jilid 3: Kemukjizatan Pengobatan Dan Makanan - [Tidak Terdaftar] (Sapta Sentosa, 2009)
Ensiklopedia Mukjizat Al-Qur'an Dan Hadis Jilid 3: Kemukjizatan Pengobatan Dan Makana